2017
DOI: 10.1093/cid/cix621
|View full text |Cite
|
Sign up to set email alerts
|

Universal Screening With Use of Immunoglobulin G Avidity for Congenital Cytomegalovirus Infection

Abstract: Maternal screening using CMV IgG and AI can identify pregnancies with CCI from primary infection, but overlooks a number of those from nonprimary infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 36 publications
0
42
2
4
Order By: Relevance
“…However, absence of detectable CMV IgM in the mothers' sera does not rule out primary CMV infection. 1,19,23 BaAlawi et al reported that a concordance of low CMV IgG AI values and CMV IgM positivity of 91% among five ELISA kits, varying between 75% and 93% for high AI values and IgM negativity. 17 Further, high CMV IgM titers reportedly correlate well with low CMV IgG AI values.…”
Section: Discussionmentioning
confidence: 99%
“…However, absence of detectable CMV IgM in the mothers' sera does not rule out primary CMV infection. 1,19,23 BaAlawi et al reported that a concordance of low CMV IgG AI values and CMV IgM positivity of 91% among five ELISA kits, varying between 75% and 93% for high AI values and IgM negativity. 17 Further, high CMV IgM titers reportedly correlate well with low CMV IgG AI values.…”
Section: Discussionmentioning
confidence: 99%
“…And yet protection of seronegative women remains an important goal given the equal contributions of transmissions in the seronegative and seropositive settings to cCMV infections in developed countries. may miss the identification of congenital CMV transmission cases in the setting of nonprimary maternal infection (51). Further support for the idea of a role of neutralizing antibodies in reducing the risk of placental HCMV transmission comes from studies demonstrating that neutralizing titers induced by the HCMV pentameric complex (PC; gH/gL/UL128-131A) against epithelial-cell-tropic viruses are strongly associated with reduced congenital CMV transmission in the setting of nonprimary congenital CMV transmission in HIV/CMV-coinfected pregnant women (48,52).…”
Section: Congenital CMV Transmission In Acutely and Chronically Hcmv-mentioning
confidence: 99%
“…By contrast, a prospective cohort study of 2193 pregnant women at low risk showed that the prediction accuracy for congenital CMV infection of maternal screening based on a CMV IgG AI of less than or equal to 45% or less than 35% was similar to that based on CMV IgM (>1.2 index) . Additionally, in this study, 10 (0.5%) of the 2193 pregnant women had newborns with congenital CMV infection, and three of these were born to mothers who had primary infection during pregnancy (as defined by a CMV IgG AI of <35% and/or a CMV IgM index of >1.2 or the detection of CMV IgG seroconversion).…”
Section: Maternal Screening For Predicting Congenital CMV Infectionmentioning
confidence: 99%
“…Figure shows a proposed screening algorithm for congenital CMV infection based on the results of our prospective cohort studies …”
Section: Maternal and Neonatal Screening Algorithm For Congenital CMVmentioning
confidence: 99%